Pengaruh Gaji Dan Kepemimpinan Terhadap Komitmen Kerja Karyawan PT. Horas Beringin Makmur, Lubuk Pakam - Aidil Putra; Leoni Ginting (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Salary is the main form of payment given to employees for work done. Payments are made every month. Leadership is an effort of a leader to be able to realize individual goals or organizational goals. Work commitment is a condition of an employee who sides with the company and has a desire to maintain his membership in a particular company. The population in this study were all employees in the company, amounting to 45 people. The sample in this study amounted to 45 people. This research used questionnaire to obtain respondents’ answers. Hypothesis test results partially indicate that salary variable significantly influence the work commitment of employees of PT. Horas Beringin Makmur, Lubuk Pakam. Hypothesis test results partially indicate that leadership variable significantly influence the work commitment of employees of PT. Horas Beringin Makmur, Lubuk Pakam. Simultaneous hypothesis test results show that salary and leadership variables significantly influence the work commitment of employees of PT. Horas Beringin Makmur, Lubuk Pakam